Pengaruh Motivasi dan Disiplin Kerja Terhadap Kinerja Karyawan PT.Kahatex - M. Ardi Nupi Hasyim; Germanus Ignasius Loyola Maje; Vina ' Alimah; Shintya Ayu Putri Priyadi (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2020)
The study aims to determine the effect of employee motivation on PT. Kahatex, the influence of employee work discipline at PT. Kahatex, as well as motivation and work discipline towards employees at PT. Kahatex. The data analysis method in this study uses the casual association method and uses a quantitative approach with quantitative data processing techniques with data processing techniques using multiple regression analysis. The data collection technique used was a questionnaire. Questionnaires distributed to employees of PT. Kahatex. Measurements were made with a Likert on a scale of one to five. The results of this study indicate that when viewed from a partial test (t) it can be seen that the results of the t value (count) is 1,782 0.05. it means that the motivation variable does not affect the performance of the employees of PT. Kahatex. Judging from the partial test (t) can be known the results of the t value (count) of 0.569 0.05. it means that the work discipline variable does not affect the performance of the employees of PT. Kahatex. While seen from the simultaneous test (F) it can be seen that the significance value for motivation of Work Motivation (X1) and Work Discipline (X2) on Employee Performance (Y) is 0,000 <0.05 and F (count) 12,706> F (table) 3 , 30, Undeniably As H3 is accepted which is intended as Work Motivation (X1) and Work Discipline (X2) simultaneously on Employee Performance (Y).